Preparation of quaternary solution processed chalcogenide thin films using mixtures of separate As40S60 and Ge20Sb5S75 glass solutions - Jančálek, Jiří; Šlang, Stanislav; Kurka, Michal; Pálka, Karel; Vlček, Miroslav (Elsevier Science BV, 2021)
In this work, the chalcogenide glass thin films of As-Ge-Sb-S system were prepared in specular optical quality by spin-coating from mixtures of separate As40S60 and Ge20Sb5S75 glass solutions. The five compositions were studied in total (0, 25, 50, 75 and 100 at.% of As40S60) to examine the possibility of deposition of quaternary chalcogenide glass thin films from mixture of simpler compositions solutions. The composition, organic residual content, structure, thickness, surface roughness, optical properties and chemical resistance of prepared films were studied in dependence on annealing temperature (up to 180C) and targeted composition. Thermally induced structural changes resulted in thin films with high optical quality and chemically stable polymerized glass structure. Physico-chemical properties of prepared mixed compositions thin films showed nearly linear combination of properties observed on As40S60 and Ge20Sb5S75 thin films.
Příprava kvarterních z roztoku připravených chalkogenidových tenkých vrstev s využitím směsí skelných roztoků As40S60 a Ge20Sb5S75
Keywords: chalcogenide; thin films; spin-coating; solution mixture; chalkogenidy; tenké vrstvy; spin-coating; směsi roztoků